2019
DOI: 10.1016/j.jclepro.2018.10.257
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater ecotoxicity assessment of pesticide use in crop production: Testing the influence of modeling choices

Abstract: Pesticides help to control weeds, pests and diseases contributing, therefore, to food availability. However, pesticide fractions not reaching the intended target may have adverse effects on the environment and the field ecosystems. Modeling pesticide emissions and the alignment with characterizing associated impacts is currently one of the main challenges in Life Cycle Assessment (LCA) of agricultural systems. To address this challenge, this study takes advantage of the latest recommendations for pesticide emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…In cases, where spatial data are becoming available, the models should be adapted to account for spatial aspects, which is discussed e.g. in Peña et al (2018Peña et al ( , 2019. More generally, for all pedo-climatic contexts, some impacts are not adequately taken into account or not included at all in some models, such as terrestrial and marine ecotoxicity (Notarnicola et al 2017).…”
Section: (Eco-)toxicity Characterization For Tropical Conditionsmentioning
confidence: 99%
“…In cases, where spatial data are becoming available, the models should be adapted to account for spatial aspects, which is discussed e.g. in Peña et al (2018Peña et al ( , 2019. More generally, for all pedo-climatic contexts, some impacts are not adequately taken into account or not included at all in some models, such as terrestrial and marine ecotoxicity (Notarnicola et al 2017).…”
Section: (Eco-)toxicity Characterization For Tropical Conditionsmentioning
confidence: 99%
“…Human and ecotoxicological impacts relating to pesticides and other chemical emissions were identified as an important environmental impact category. Most studies addressing the environment impacts of pesticides address individual food products, such as citrus [53], strawberries [54,55], cherries [56], pineapples [57], or other crops [58], not entire diets. In this study of Australian adult daily diets, it was shown that the human and ecotoxicological impacts relating to pesticide use vary widely between individual diets and that these potential impacts are determined largely by food choice.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Within impact analyses, it would be overwhelming if all emissions were individually defined. To aggregate and simplify the results, equivalents based on impact severity (e.g., toxicity, hazard potential) are used to aggregate different environmental releases (Peña, Knudsen, Fantke, Antón, & Hermansen, 2019).…”
Section: Equivalentmentioning
confidence: 99%